Vowel shifts in Middle Wichi (Mataguayan, South America) - Nercesian, Verónica (2023)
This paper analyzes vowel shifts in Wichi (Mataguayan, South America) between the 18th and early 20th centuries, some of which contributed to the emergence of the Pilcomayeño and Bermejeño dialects. Based on a historical database and using the comparative method, we date the vowel shift over the period we have named as Middle Wichi. At the early stage of this period, the /e/ > /a/ lowering is analyzed as a sporadic change, spread across the dialects in part of the vocabulary. At a later stage, the chain shift /ɑ/ > /o/ > /u/ > /e, i/, the merger of /u/ with /e/ and /i/, and the sporadic change of /i/>/e/ lowering in some words took place in Bermejeño. The paper explores implications in the implementation of sound change, the regular changes and the lexical diffusion, in particular, in chain shifting. It also explores some connections with other Mataguayan languages in both the lowering e>a and the possible causes of the changes. Thus, the paper contributes to the historical study of the Wichi language and the Mataguayan family in the Gran Chaco area in South America.